The impacts of land use changes in the mercury flux in the Madeira River, Western Amazon - Lacerda,Luiz D. (2012)
Changes in hydrochemistry and Hg distribution in the Madeira River from Porto Velho to the confluence with the Amazon River were studied in two cruises in 1997 and 2002. Water conductivity was similar in both periods, but the pH was significantly higher in 2002, in particular along the middle reaches of the river. Total suspended matter concentrations also increased from 1997 to 2002 along the same river portion, which is a result of forest conversion to other land uses, in particular pastures and agriculture accelerated during the interval between the cruises. Dissolved Hg concentrations were similar along the river in both cruises, but particulate Hg concentrations increased significantly along the middle portion of the river, although the suspended matter from 2002 was relatively poorer in Hg compared to that from 1997. Since particulate Hg represents more than 90% of the total Hg present in the river water, there was a significant increase in the total Hg transport in the Madeira River. Although gold mining has nearly ceased to exist in the region, the remobilization of Hg from forest soils through conversion to other land uses is responsible for maintaining relatively high Hg content in the Madeira River environment.